PENGARUH ATRIBUT PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BUNDLE HANDPHONE SMARTPHONE MEREK BLACKBERRY 8530 - WIKAN DEWI, NORMASARI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The trade development today was coloring with many kinds of competition in most of sectors, especially in telecommunication sector. The application of hand phone today not only for phone and sending message, but many of the hand phone user that used it for data service. The one of Smartphone that look for by the society today is Blackberry. The Blackberry that selling well today is Blackberry Curve 8530 or that more popular in the name Blackberry Aries that was bundled with smart fren. For today Blackberry Curve 8530 be the best seller, because the price that cheap and have many good features. The results showed that the effect of product attributes and price of the Purchase Decision Bundle Brand Mobile Smartphone BlackBerry 8530 has a very strong influence in the amount of 83,6% and the remaining 16,4% is influenced by other variables beyond the variables used in this study. Keyword: Product Attribute, Price, and Purchase Decision